Costs and effects of a multifaceted intervention to improve the quality of care of children in district hospitals in Kenya - Barasa, Edwine W (Health Economics Unit, 2014)
In Kenya, an intervention to improve the quality of care of children was developed and tested in district hospitals. This was a multifaceted intervention employing clinical practice guidelines, training, supervision, feedback and facilitation, for brevity called the Emergency Triage and Treatment Plus (ETAT+) strategy. This thesis presents an economic evaluation of this complex intervention.